Perlindungan Hukum Korban Kekerasan Seksual terhadap Perempuan di Lingkungan Pendidikan Tinggi dengan Modus Eksploitasi Hubungan Mentor-Mentee - Sony Nurmansyah; Ahmad Jamaludin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines legal vulnerabilities and the role of institutions in addressing sexual exploitation within mentor–mentee relationships in higher education. It highlights the power imbalances that make female students particularly vulnerable to becoming victims, the gaps within the existing legal framework, and the systemic challenges that perpetuate a culture of “silencing” around this issue. Although the Sexual Violence Crime Law (UU TPKS) provides a legal basis for victim protection, its implementation in universities remains largely ineffective. This article explores the importance of stronger institutional policies, improved reporting mechanisms, and awareness programs to prevent exploitation. The study emphasizes the crucial role of universities in creating a safe and ethical academic environment by ensuring that legal actions and internal policies align to protect victims and hold perpetrators accountable.